Intravenously Administered Lidocaine and Magnesium During Thyroid Surgery in Female Patients for Better Quality of Recovery After Anesthesia. (September 2018) - Kim, Myoung Hwa; Kim, Min Soo; Lee, Jae Hoon; Kim, Sang Tae; Lee, Jeong-Rim
Abstract : BACKGROUND: Although systemic lidocaine and magnesium have been widely studied as perioperative analgesic adjuvants, they have been rarely evaluated with respect to recovery quality under the same conditions. We compared the quality of recovery 40 (QoR-40) scores of female patients who received intravenous lidocaine, magnesium, and saline during thyroidectomy to investigate their effects on comprehensive recovery from anesthesia. METHODS: In this prospective, double-blind trial, 135 female patients scheduled for open thyroidectomy were randomly assigned to the lidocaine group (group L), magnesium group (group M), or control group (group C). Immediately after induction, lidocaine (2 mg/kg for 15 minutes followed by 2 mg/kg/h) was administered in group L and magnesium sulfate (20 mg/kg over 15 minutes followed by 20 mg/kg/h) was administered in group M. Group C received an equivalent volume of saline. The QoR-40 survey was conducted on postoperative days 1 and 2. RESULTS: The mean global QoR-40 scores on postoperative day 1 were 186.3 (standard deviation, 5.5) in group L, 184.3 (4.7) in group M, and 179.4 (17.8) in group C, and there was a significant difference only between group L and group C (mean difference, 6.9; adjusted P = .018). Among the 5 dimensions of QoR-40, emotional state, physical comfort, and pain were superior in group L compared to group C. CONCLUSIONS: Lidocaine administered intravenously during anesthesia led to better quality of postoperative recovery measured by QoR-40 compared with the group C. Magnesium was found to be insufficient to induce any significant improvement with the dose used in the present study.